TANTANGAN SUMBER DAYA MANUSIA DI PEMERINTAHAN LOKAL (Analisa Tentang Tantangan SDM Pemerintahan Lokal Indonesia dalam persaingan MEA) - Rahman, Abdu (Aspirasi: Jurnal Ilmiah Administrasi Negara, 2016)
With the mutual recognition arrangements (MRAs) that was agreed in the ASEAN Framework Agreement on Services (AFAS) in 1995, which includes AFTA, CAFTA, APEC and the MEA which have been completed in 2015, forcing Indonesia especially at the local government must be prepared with the ability competitive global HR and interactive global communication in order to maintain maximum competitiveness, especially in the preparation of expert manpower. Underdevelopment Indonesian expert manpower of other developing countries affects the competitiveness and resilience of Indonesian economy. Ready workforce prepared by the government is only non-skill manpower and semi-skill which of course will impede chances of Indonesia in the face of liberalization of expert manpower in the ASEAN economic community. It can be seen from the figure for unskilled workers (non-skill) which reached 55.31%, which are spread throughout the country and became the mainstay of Indonesian non-oil foreign exchange, and the non-skill manpower of most concern are not included in the liberalization of labor into agreements in the area of ASEAN economic community. In addition, the challenges facing Indonesia local governments especially area of east Indonesia, such as the Province of Papua, Gorontalo, Sulawesi and NTT-NTB are areas that actually have the potential of great Natural Resources but lack of infrastructure development, such as roads, electricity, clean water and housing make these areas are always lagging and backward.